Trends and Patterns of Voluntary and Involuntary Single Women in Nepal - Sigdel, Uddhav; Adhikari, Laxmi (Journal of Nepalese Studies, 2025)
The analysis of single women in Nepal, using census data, plays an important role in understanding the country’s demographic and socio-economic context. The study explored the demographic and socio-economic conditions of single women at both national and sub-national levels. Singlehood—whether by choice (voluntary) or due to circumstances (involuntary)—was found to shape the structure of society. The research focused on women aged 10 years and above (N=12,439,247) as recorded in the 2021 National Population and Housing Census (NPHC). Women were grouped into five categories based on their marital status. Data from NSO, 2024, to analyze the trends and patterns of single women. Findings of the study revealed that there is a rise in both voluntary and involuntary singlehood since 2001. The increase in singlehood by choice is largely driven by women’s empowerment, while involuntary singlehood is linked to demographic and socio-economic vulnerabilities. The study highlights the need for policies that address the challenges faced by involuntary single women, particularly social protection programs.